2022
DOI: 10.1111/ijfs.15785
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the miRNAs and their target genes involved in fresh‐cut potato browning inhibition by nitrogen

Abstract: Summary Browning decreases the quality and shortens the shelf life of fresh‐cut potato, causing enormous economic losses. This study indicated that nitrogen treatment could inhibit this browning process. However, whether microRNAs (miRNAs) are involved in inhibiting the fresh‐cut potato browning by nitrogen remains unclear. Therefore, nine small RNA libraries were constructed and performed high‐throughput sequencing using fresh‐cut potatoes from control and nitrogen‐treated for 1 h groups at 25 °C to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Current research on miRNAs is mainly focused on cancer-specific miRNAs and related target genes in order to elucidate the biological mechanism of cancer occurrence. 17 It has been found that many miRNAs are dysregulated in various types of malignant tumors, and are closely related to tumor diagnosis, staging, progression, prognosis, and clinical treatment efficacy. 18 Previous studies have shown that the levels of miRNA-18a, miRNA-130a, and miRNA-92a are elevated in the serum of patients with various cancers including CC, 19,20 but the research on whether miRNAs can be used as serological detection indicators of CC is still limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current research on miRNAs is mainly focused on cancer-specific miRNAs and related target genes in order to elucidate the biological mechanism of cancer occurrence. 17 It has been found that many miRNAs are dysregulated in various types of malignant tumors, and are closely related to tumor diagnosis, staging, progression, prognosis, and clinical treatment efficacy. 18 Previous studies have shown that the levels of miRNA-18a, miRNA-130a, and miRNA-92a are elevated in the serum of patients with various cancers including CC, 19,20 but the research on whether miRNAs can be used as serological detection indicators of CC is still limited.…”
mentioning
confidence: 99%
“…A large amount of evidence shows that about 60% of human protein‐coding genes may be regulated by miRNA, and miRNA has been confirmed to play an important role in various cellular biological processes, such as cell proliferation, apoptosis, migration, invasion, and tumorigenesis, 14,15 like miRNA‐18a, miRNA‐130a, miRNA‐92a, miRNA‐100, 16 etc. Current research on miRNAs is mainly focused on cancer‐specific miRNAs and related target genes in order to elucidate the biological mechanism of cancer occurrence 17 . It has been found that many miRNAs are dysregulated in various types of malignant tumors, and are closely related to tumor diagnosis, staging, progression, prognosis, and clinical treatment efficacy 18 …”
mentioning
confidence: 99%